Is it possible to standardize the treatment of primary spontaneous pneumothorax? Part 2: surgical methods of treatment - Rokicki, Wojciech; Rokicki, Marek; Wojtacha, Jacek; Filipowski, Marek; Dżejlili, Agata; Czyżewski, Damian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The present report provides a detailed description of the surgical methods for primary spontaneous pneumothorax (PSP) treatment, from open surgery (thoracotomy) to minimally invasive procedures (video-assisted thoracoscopic surgery – VATS). It describes the methods of preventing pneumothorax recurrence, including partial or complete resection of the parietal pleura and chemical pleurodesis with VATS. The pros and cons of each method are presented. The paper also discusses new techniques for diagnosing pneumothorax, such as fluorescein-enhanced autofluorescence thoracoscopy (FEAT) and infrared thoracoscopy. Finally, the authors propose their own algorithm for the treatment of PSP.